Role of Chemical Structure of Support in Enhancing the Catalytic Activity of a Single Atom Catalyst Toward NRR: A Computational Study - Senthamaraikannan, Thillai Govindaraja; Kaliaperumal, Selvaraj; Krishnamurty, Sailaja (Frontiers in Chemistry, 2021)
Using periodic density functional theory based methodology, we propose a potential catalytic system for di-nitrogen activation, viz single metal atoms (Mo, Fe and V) supported on graphene based sheets. Graphene based sheets show an excellent potential towards the anchoring of single atoms on them (Mo, Fe and V) with adsorption energies ranging between 1.048 – 10.893 eV. Factors such as defect, BN doping etc are noted to enhance the adsorption energies of single metal atoms on the support. The adsorption of dinitrogen molecule on metal atom anchored graphene based supports is seen to be highly favorable, ranging between 0.620 – 2.278 eV. The adsorption is driven through a direct hybridization between the d orbitals of the metal atom (Mo, Fe and V) on support and the p orbital of the molecular nitrogen. Noticeably, BN doped graphene supporting a single metal atom (Mo, Fe and V) activates the N2 molecule with a red shift in the N–N stretching frequency (1597 cm-1 as compared to 2330 cm-1 in the free N2 molecule). This red shift is corroborated by an increase in N–N bond length (1.23 Å from 1.09 Å) and a charge transfer to N2 molecule from the catalyst.